Analisis Dampak Compound Interest pada Investasi Jangka Panjang Studi Empiris pada Reksa Dana Saham - Nathasya, Tiara; Nicko Albart (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study analyzes the impact of compound interest on long-term investments, focusing on equity funds. Using quantitative simulations, it evaluates how consistent monthly investments grow over time through the effect of compounding interest. Key assumptions include a fixed monthly investment of IDR 1,000,000 and an average annual return of 10%. The results demonstrate exponential investment growth, with significant increases in final values over 10, 20, and 30 years. For instance, after 30 years, the total investment grows to more than six times the principal amount, underscoring the power of compounding interest. The findings highlight the importance of starting investments early and maintaining discipline, particularly in long-term financial planning. This study provides practical recommendations for novice investors to leverage equity mutual funds as a high-return instrument, despite associated risks, to maximize long-term wealth accumulation. Limitations include the exclusion of market volatility, inflation, and other costs, which could influence real-world outcomes. keywords: Compounding Interest, Equity Funds, Long-Term Investment